Roma criminality in Slovakia. An introduction to the problem - Mlýnek, Jaromír (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article concerns the problem of crime related to the Roma minority in Slovakia. The text presents the most important socio-cultural issues that affect the occurrence of crime perpetrated against Roma. It also discusses crime committed by Slovak Gypsies. The paper also comprises photographic documentation.
Keywords: Słowaccy Romowie; Republika Słowacji; przestępczość